Hubungan Pengetahuan Dengan Self-Efficacy Dalam Melakukan Deteksi Dini Tanda Bahaya Oleh Ibu Nifas - Faista Ardani; Rita Yulifah; Sheilla Tania Marcelina; Rudi Hamarno (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The risk of death in the mother is 60% after giving birth and almost 50% of deaths during the postpartum period occur in the first 24 hours of delivery. The causes of death in postpartum mothers are bleeding, eclampsia and infection. The better the postpartum mother's knowledge, the higher the postpartum mother's self-efficacy in detecting early danger signs during the postpartum period. The aim of this research is to determine the relationship between knowledge and self-efficacy regarding early detection of danger signs during the postpartum period in the Kepanjen Community Health Center Work Area. This research design uses correlational analytics with a cross sectional approach carried out on a sample of 44 respondents. This research sample was taken using a positive sampling technique. The data collection instrument used was a questionnaire. The research results show that the majority of postpartum mothers have good knowledge and high self-efficacy. The statistical test results show a significance figure of 0.000 using the Spearman Rank Test with a significance level of α > 0.05. The results of the research show that there is a significant and very strong relationship between knowledge and self-efficacy in early detection of danger signs by postpartum mothers with a coefficient value of 0.760 with a positive relationship direction. Postpartum mothers' good knowledge and high self-efficacy about the signs of the dangers of postpartum contribute significantly to postpartum mothers' ability to detect early and overcome emerging health problems.